Education, Practice, and Research in Nursing Terminology: Gaps, Challenges, and Opportunities - Park, H.-A.; Cho, I. (Yearbook of Medical Informatics, 2009)
Objectives To provide an overview of nursing terminology education, research, and clinical use, to identify and analyze any gaps therein, and to propose ways to close those gaps.Methods We conducted an extensive Internet and literature search to establish the current status of nursing terminology education, research, and clinical use. We also surveyed 40 experts in nursing terminology from 15 countries to obtain more detailed information on nursing terminology education and clinical use.Results We found that there are gaps in nursing terminology education, research, and use, with the area of research being the most advanced. Nursing terminology is not taught widely in either informatics or nursing programs. Where it is taught, it constitutes only up to several hours of an informatics or nursing course. Research into nursing terminology has been very active, focusing mainly on the development and evaluation/validation of nursing terminology, using reference terminology models, and mapping between these and nursing terminologies. However, little research has been carried out on the use of nursing terminologies in clinical information systems. In addition, there are very few systems in which a standardized nursing terminology has been implemented.Conclusion In order to close the gaps in nursing terminology education, research, and clinical use, qualified personnel are required to educate potential users as to the importance of terminology-based information systems for semantic interoperability. In addition, more research is required into the implementation of nursing terminologies in information systems, and we must demonstrate the usefulness and effectiveness of nursing terminology-based information systems.
Keywords: Nursing terminology; nursing informatics; gap analysis; education; research; clinical practice